The Effect of Virtual Laboratory using Ethnoscience Concept “Mangeppi Agara” on Students’ Digital Literacy and Science Literacy - Romi Adiansyah; Astuti Muh. Amin (Jurnal Penelitian Pendidikan IPA, 2026)
In this digital age, digital literacy and science literacy are key to comprehending and applying knowledge efficiently. However, modern science education often overlooks local wisdom and ethnoscience, which are rich in cultural values and traditions. Ethnoscience studies can provide material for creating virtual laboratories to help students increase their digital literacy and science literacy. The purpose of this research is to analyze the effect of virtual laboratories using the "mangeppi agara" ethnoscience concept on students' digital and scientific literacy. The present study employed a quasi-experimental design to generate a virtual laboratory that embodies the ethnoscience idea "Manggeppi Agara". The product comprises simulations/demos, videos, assessments, and images created with Augmented Reality (AR) technology. The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was implemented to produce the laboratory. The product was examined by experts in the field and tried out to 202 biology students. The result showed that the laboratory was valid. The research instruments consisted of tests to assess pupils’ digital and science literacy. The study’s findings revealed that employing a virtual laboratory based on the "Manggeppi Agara" Ethnoscience idea improved students’ digital literacy and science literacy. virtual laboratory using the Etnosains concept "Manggeppi Agara" had an impact on students’ digital literacy and science literacy. These findings are expected to help advance the quality of learning design in university and enhance students’ science competencies in the face of rapid global change.